Determinants of Economic Growth in Indonesia: Evidence from an ARDL Bounds Test - Mochammad Nurul; Shemelis Kebede Hundie (Universitas Airlangga, 2026)
Background: Over the past five decades, Indonesia's economic development has been influenced by rapid growth and recurring structural challenges. Analyzing the factors that determined GDP during this period can provide insights into sustainable economic policy. Objective: This study examines the primary factors that have influenced Indonesia's economic growth from 1970 to 2021. The study focuses on international trade, population dynamics, health outcomes, and urbanization. Methods: We apply the autoregressive distributed lag (ARDL) model to time-series data from the World Development Indicator (WDI). We test for stationarity using the Augmented Dickey-Fuller (ADF) test in GRETL, and we perform ARDL estimation, including cointegration and short- and long-term dynamic relationships, in EViews. Results: Inflation, population growth, urbanization, and the dependency ratio negatively impact GDP. Meanwhile, exports (coefficient = 0.242) and air passenger traffic (coefficient = 0.190) positively impact long-term growth. Short-term dynamics reveal delayed adjustments, with the system approaching equilibrium at a rate of 65.4% per period. Diagnostic tests confirm the model's robustness, supporting its use in policy planning and forecasting. Keywords: ARDL model, economic growth, Indonesia, time-series analysis, urbanization